(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This article investigates the effectiveness of CLIL (Content and Language Integrated Learning) in foreign language education. CLIL is an innovative pedagogical approach where students learn a subject and a foreign language simultaneously. This dual-focused method enhances language proficiency while promoting cognitive, cultural, and content knowledge. The study explores theoretical foundations of CLIL, its application in foreign language classrooms, the role of teachers, and the benefits and challenges of this methodology. Practical examples and case studies are provided to illustrate the implementation of CLIL in real educational settings